REDUCTION OF EARLY MORTALITY AND OF CARDIAC RUPTURE IN ACUTE TRANSMURAL MYOCARDIAL INFARCTION BY INTRAVENOUS STREPTOKINASE - Figueras, J; Cortadellas, J; Monasterio, Y (Thrombosis and Haemostasis, 1987)
Patients (Pts)≤ 70 years old with a first transmural AMI of ≤ 4h (164±55 min) were randomized to receive (Group I,GI n=105) or not (GII, n=102) i.v. streptokinase (SK, 840.000U in lh).Contrc ST segment elevation and at lh and 24h after admission were comparable in both groups. Coronary arteriography performed within 15 days showed a recanalization rate of 64% in GI and of 27% in GII (p<0.001)but an incidence of severe stenosis (≥90<100%) higher in GI (46 vs 22%, p<0.01).Recanalized Pts presented an earlier peak of MB creatin kinase in GI (12 vs 16h p<0.01) as well as in GII (15 vs 21h, p<0.002). The incidence of pericarditis was lower in GI (14 vs 35%, p<0.001). Although hospital mortality was comparable in the 2 groups (GI,8% vs GII,11%), early mortality, <5 days, was lower in GI (2 vs 10%, p<0.02). Sudden electromechanical dissociation was the mechanism of death in 12% of patients from GI and in 77% of those from GII and it was associated with left ventricular free wall rupture in each of the 5 autopsied cases but in none of the 5 autopsied cases who died without electromechanical dissociation During a follow-up of 20±11 months (1-36) , mortality an incidence of angina was similar in both groups but reinfarction rate was higher in GI (16 vs 1%, p<0.05).It is concluded that: 1) In contrast with the changes in ST .segment, an early MB creatin kinase peak is a reliable marker of reperfusion; 2) i.v. SK lowers the incidence of pericarditis and of early mortality reducing the incidence of cardiac rupture; and 3) It is conceivable that early treatment of critical residual stenosis will reduce in hospital mortality and reinfarction in these Pts.